The Golly sisters go West - Byars, Betsy Cromer; Truesdell, Sue (New York : HarperTrophy, 1985)
May-May and Rose, the singing, dancing Golly sisters, have several adventures while traveling west by covered wagon, entertaining people along the way.
Keywords: Children's stories, American; Frontier and pioneer life -- Fiction; Western stories